The Impact of Academic Publication: Inequity for Women in Behavior Analytic Journals - Krebsbach, Jennifer M. (Frontiers in Sociology, 2022)
The number of women in higher education has increased over the past few decades but are still not at an equal level to their male counterparts, especially at the tenured level. One area of note within the tenure process is research. This area is highly valued by certain universities and could shed light on discrepancies in the number of female faculty as the faculty position becomes more prestigious. The author downloaded 21 years of publication data for seven prestigious behavior analytic journals and used quantitative methods to determine if the rates of publication differed between a previous study and today. There were 8,778 final articles yielding 27,225 authors in total. Data showed that women are represented more frequently overall, across time and all journals, less frequently in prestigious authorship positions, and more often when the sex of the editor at the time of publication was also female. While women's participation has increased over time, and since the original study, there is still disproportionate representation compared to the entirety of the field, in the order of authorship positions, and for editor-in-chief positions.